FROM SAIRAM TO KUBACHI: SOCIAL AND CULTURAL CONTEXT OF THE FIFTEENTH CENTURY DISHWARE EPIHGRAPHY - Babadzanov, Bahtiar Miraimovic (History, Archeology and Ethnography of the Caucasus, 2024)
This study attempts to fill the gaps in the research on 15th-century glazed ceramicware found across a vast region extending from Sairam in Southern Kazakhstan to Kubachi and the southern borders of Iran, as published in numerous articles and monographs. This paper focuses primarily on the inscriptions adorning these ceramics, which occasionally include the names of the artisans, dates, and places of manufacture. In our paper, we present a previously unpublished fragment of inscribed dishware from Old Tashkent. The study reveals that the majority of inscriptions on ceramics from this period are excerpts from Sufi poetry. We have successfully identified the authors of these poems. Previous publications typically provided only cursory readings and translations of the epigraphic content without attempting to identify the authors or interpret the texts within cultural contexts or as potential reflections of Sufi ideology. We argue that a “Sufi reading” of these texts significantly alters their interpretation and translation. However, when isolated from their original poetic context, the meaning of these fragments often becomes utilitarian, a part of gift-giving wishes. This transformation does not necessarily indicate a complete desecration of the original text, but rather reflects the cultural demands and codes of the typical consumers of this ceramicware within the framework of a “folk perception” of Sufi poetry.
Keywords: epigraphic on household ceramics; Sufi poetry; culture of artisan village